Measuring murine chromosome orientation in interphase nuclei. (17th April 2015) - Righolt, Christiaan H.; Schmälter, Ann‐Kristin; Kuzyk, Alexandra; Young, Ian T.; van Vliet, Lucas J.; Mai, Sabine
Abstract The nuclear architecture of a cell may change as a result of various diseases, including cancer. A variety of nuclear features are, therefore, of interest to cell biologists. Recently, several studies have investigated the orientation of chromosomes in the interphase nucleus either visually or semi‐automatically. In this article an automated method to measure this orientation is presented. The theoretical difference between performing these measurements in two and three dimensions is discussed and experimentally verified. The results computed from measurements of murine nuclei correspond with results from visual inspection. We found significant differences in the orientation of chromosome 11 between nuclei from a PreB cell line of BALB/c origin and primary B nuclei from congenic [T38HxBALB/c]N wild‐type mice. Since our new automatic method concurs with both the visual and semi‐automatic methods, we conclude that the automatic method can replace these methods in assessing chromosome orientation. © 2015 International Society for Advancement of Cytometry